Perlindungan Hukum Kekayaan Intelektual Hak Cipta atas Motif Batik Krakatoa Di Kota Cilegon - Sulasno Sulasno (Universitas Serang Raya, 2020)
This research aims to find out the problems and solutions that can be done to overcome the problem of the protection of batik copyright law in the city of Cilegon based on law number 28 of 2014 concerning copyright.The formulation of the problem and the purpose of this paper is to see how the existence of batik in the city of Cilegon, businesses and any obstacles faced by the Cilegon city government in providing legal protection for the batik. in addition, the purpose of this study is to provide knowledge that the importance of other legal instruments that are technical. The intended legal device can be in the form of a Regional Government Regulation that regulates the protection of traditional batik art creations including folklore. The research method used is the empirical juridical approach method, where the procedure begins by examining secondary data first, then proceed with examining primary data in the field. The specifications of this study are analytical descriptive. Sources and types of data, consisting of primary data and secondary data. Data analysis is done qualitatively considering the data collected is analytical descriptive. Keywords: Law; Protection; Copyright; Batik; Krakatoa.